Analisis Kemampuan Membuat Tempat Pensil Dari Kain Perca Pada Siswa Laki-Laki Kelas VII SMP Negeri 31 Medan - Siti Maisyarah Hasibuan; Juliarti Juliarti (Journal on Education, 2025)
In making craft products from patchwork fabrics, the abilities of male students are still not optimal compared to female students. This is due to the lack of interest of male students in practice because they assume that patchwork fabric crafts are women's work, from year to year the products produced are the same, male students are less active and less creative in making craft products. The purpose of the study was to determine the ability to make pencil cases from patchwork fabrics in male students. The research was conducted in August 2019. The research design used was descriptive research. The population in this study were male students in grade VII of SMP Negeri 31 Medan with a total of 143 students. The research samples were male students of class VII-4 totaling 18 students and VII-5 totaling 15 students. The data collection tool used was an observation sheet observed by 5 observers with an assessment grid consisting of 13 indicators. The results of the ability to make pencil cases from patchwork fabrics in male students of class VII SMP Negeri 31 Medan obtained 64,6% of students have very good abilities, 29,1% of students in the good category, 3,5% of students in the less category, and 2,8% of students in the sufficient category. When viewed from 13 aspects of the assessment, the highest ability is in the aspect of measuring the length of hemp rope with an average score of 94,2 and the ability to adjust the color of decorative buttons with the color of the fabric with an average value of 93,7.